Chronic low back pain patients walk with locally altered spinal kinematics. (26th July 2017) - Christe, Guillaume; Kade, François; Jolles, Brigitte M.; Favre, Julien
Abstract: Various studies have reported alterations of spinal kinematics in patients with chronic low back pain (CLBP) during gait. However, while recent findings stressed the importance of multi-segment analysis, most of prior gait studies modelled the lumbar spine as one segment, when it was not the entire trunk that was considered as a single segment. Therefore, there is a need for comprehensive multi-segment research that could improve our understanding of CLBP pathomechanism and thus possibly contribute to better care for CLBP. This study aimed at characterizing the angle patterns at the lower lumbar (LLS), upper lumbar (ULS), lower thoracic (LTS) and upper thoracic (UTS) joints in the three anatomical planes and at comparing CLBP patients and asymptomatic subjects. Spinal kinematics of 11 CLBP patients and 11 controls was measured using a marker-based motion capture system and described according to a previously proposed multi-segment biomechanical model. Characteristic patterns were observed at the UTS, LTS and ULS joints in the transverse plane and at the UTS, ULS and LLS joints in the frontal plane. CLBP patients walked with smaller frontal-plane LLS range of motion than controls. The results also suggested that patients had more asymmetrical LTS motion in the transverse plane. In conclusion, this work extended prior literature by showing specific CLBP-related alterations in multi-segment spinal kinematics during gait. Further research is necessary to understand the factors influencing kinematics alterations and how treatment strategies might improve motor behaviour in CLBP patients.